Do Vouchers for Job Training Programs Help? - World Bank (World Bank, Washington, DC, 2012)
Youth unemployment is a problem in many developing countries, where labor market opportunities may be further squeezed by rapid rural migration into big cities, the cost of higher education and job seekers' limited information about the best opportunities. Policymakers and aid organizations trying to reduce youth unemployment have a variety of approaches they can use, including vocational training programs to give job seekers necessary skills to be employed. But what works best is still not clear: should governments subsidize job training programs for young adults? Should they limit subsidies to public sector programs or include the private sector? Do government-run and private institutions differ in their ability to attract students and prepare them to find a job? What roles do outside factors, such as distance to a school, play in a young adult's decision to enroll in a training program? In Kenya, the World Bank supported a special voucher program for young adults to evaluate demand for vocational training and the impact of training on job seekers. The evaluation showed that offering young adults vouchers that cover program costs does encourage young adults to enroll, and that those who can use the voucher for a private training program are more likely to sign up and stay in school. The results of the study are in line with research done in Latin America, indicating the benefits of making vocational training more widely available in developing countries. While further research of this program is planned in Kenya, the initial evaluation does show that vouchers for vocational schools especially when private sector schools are included can be an effective way to give job seekers employable skills.